Superionic Conduction in Substoichiometric LiAl Alloy: An Ab Initio Study - Cucinotta, C.; Miceli, G.; Raiteri, Paolo; Krack, M.; Kuhne, T.; Bernasconi, M.; Parinello, M. (The American Physical Society, 2009)
Based on the new ab initio molecular dynamics method by Kuhne et al. [Phys. Rev. Lett. 98, 066401 (2007)], we studied the mechanism of superionic conduction in substoichiometric Li-poor Li1xAl alloys by performing simulations at different temperatures for an overall simulation time of about 1 ns. The dynamical simulations revealed the microscopic path for the diffusion of Li vacancies. The calculated activation energy (0.11 eV) and the prefactor (D0=6:9 x 10-4 cm2/s) for Li diffusivity via a vacancy-mediated mechanism are in good agreement with experimental NMR data. The calculation of the formation energies of different defects-Li and Al Frenkel pair and Li antisites- revealed that only Li vacancies and LiAl antisites are present in the stability range of the Zintl phase -0.1 <x<0.2.